Evaluasi Program Model CIPP Pada Lembaga Konseling Mahasiswa UIN Fatmawati Sukarno Bengkulu - Naser, Muhammad Nikman (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
This study aimed to determine the application of the student counseling service program at the Student Counseling Institute of the Syariah Faculty of UIN FAS Bengkulu in terms of the CIPP evaluation model (Context, Input, Process, and product). This study is evaluative research with mixed research methods. Data sources The research is 1 Internal Supervisory Unit, 1 Dean, 5 Consultants, and 60 students. Data collection methods use interviews, questionnaires, and documentation. Data analysis uses qualitative data analysis techniques and percentage descriptive data analysis. The results show that the evaluation results on the context component, input, and the process is in the good enough category while the product component is in a good category. The conclusion from this study is that the evaluation of the implementation of the student counseling program with the CIPP evaluation model is fairly good.